A key to species of genus Malcus Stål, with descriptions of four new species from China (Hemiptera: Heteroptera: Malcidae) - Wang, Shujing; Bu, Wenjun (Zootaxa, 2020)
Four new species of Malcus Stål are described and illustrated, Malcus alatus sp. nov., Malcus bacillus sp. nov., Malcus externus sp. nov. and Malcus planus sp. nov.. The male of Malcus gibbus Zheng, Zou & Hsiao, 1979 is described for the first time. A revised key to species of Malcus of the world is provided.